Measurement of Linear Attenuation Coefficient of Tc-99m using Planar Gamma Camera Image (Bangladesh Journal of Nuclear Medicine, 2015)
Introduction: Attenuation is one of the most important factors which have an impact on the accuracy on quantitation of activity when using gamma camera image in a medium. Due to attenuation a number of photons are lost and there is also loss of counts which otherwise would have been included in the images. The purpose of this study is to estimate the linear attenuation coefficient for Tc-99m with water filled phantom using conjugate view method and transmission method and compare the obtained measurements with the reference values. Materials and Methods: To determine the linear attenuation coefficient of radionuclide Tc-99m using conjugate view method, the sensitivity of the gamma camera was determined. 30 MBq of Tc-99m was taken which was measured in dose calibrator and gamma camera images were acquired. Then the sensitivity was calculated as CPS/MBq. A Jaszczak phantom was filled up with water and a small sized cylindrical container filled with activity of 30 MBq Tc-99m liquid was placed inside the Jaszczak phantom centrally. The phantom was scanned on a dual head gamma camera and the images were taken and counts from the images were estimated. After estimation of all values, the linear attenuation coefficient was calculated using conjugate view formula. The linear attenuation coefficient was also measured from the transmission imaging. The transmission factor (TF) was determined by measuring the ratio of count rates obtained with Tc-99m under gamma camera, with and without the phantom. Results: The linear attenuation coefficient was calculated 0.1467 ± 0.0057 from conjugate view method and 0.1483 ± 0.0023 from transmission measurements. Both results were found within ±5% of the established value (0.15 cm-1). Conclusions: Correction for attenuation is required for the accurate estimation of activity. For conjugate view method, the attenuation coefficient was measured with a known activity of Tc-99m. The attenuation coefficient was also estimated by transmission measurements. The accuracy of the activity measurement is highly dependent on the accuracy of the attenuation coefficient used in the calculation. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22493 Bangladesh J. Nuclear Med. 17(1): 61-66, January 2014